Characteristics of Immune Response to Tumor‐Associated Antigens and Immune Cell Profile in Patients With Hepatocellular Carcinoma. Issue 2 (31st December 2018) - Inada, Yuki; Mizukoshi, Eishiro; Seike, Takuya; Tamai, Toshikatsu; Iida, Noriho; Kitahara, Masaaki; Yamashita, Tatsuya; Arai, Kuniaki; Terashima, Takeshi; Fushimi, Kazumi; Yamashita, Taro; Honda, Masao; et al.
Abstract : Host antitumor immune responses may be different between hepatocellular carcinoma (HCC) caused by metabolic disorders and HCC associated with hepatitis virus infection. In this study, we examined the immune response of tumor‐associated antigen (TAA)–specific T cells and immune cell profile in patients with HCC separated by cause. Thirty‐two patients with hepatitis B virus (HBV)–related HCC, 42 patients with hepatitis C virus–related HCC, and 18 patients with nonalcoholic steatohepatitis (NASH)–related HCC were analyzed. The frequencies of TAA‐specific T cells, the expression levels of surface markers on each immune cell, and the expression of each TAA in HCC tissue were measured. The immune response to TAA and immune cell profile were markedly different among the three groups. The immune response to TAA in the NASH‐related HCC group was weaker than the responses in the other two groups. In patients with NASH‐related HCC, the frequencies of effector regulatory T cells (eTregs) and cluster of differentiation 8–positive (CD8 + ) T cells strongly expressing cytotoxic T‐lymphocyte antigen (CTLA)‐4 were high. The frequency of CD8 + T cells strongly expressing programmed cell death 1 was the highest in patients with HBV‐related HCC. Among these immune cell profiles, the frequencies of C‐X‐C motif chemokine receptor 3 + eTregs and CTLA‐4 + CD8 + T cells were inversely correlated with the strength of the TAA‐specific T‐cell immune response, and the restoration of TAA‐specific T‐cell responses by anti‐CTLA‐4 antibody was observed. Conclusion : The immune response to TAA were markedly different among the three groups, and a correlation with the immune cell profile was observed, suggesting that development of immunotherapy based on the etiology of HCC may lead to more effective treatment outcomes.